ECHOES OF TRADITION: THE GRAND BASANT FESTIVAL OF LAHORE DARBAR - Renu Bala (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Maharaja Ranjit Singh, proudly known as Sher-i-Punjab (Lion of the Punjab), was one of the outstanding figures in Indian history. On 20 August 2003, a 22-foot-tall bronze statue of Maharaja Ranjit Singh was installed in the Parliament of India. Prime Minister Atal Bihari Vajpayee unveiled the statue. In 2016, the town of St. Tropez in France unveiled the Maharaja’s bronze statue as a mark of respect. In 2020, Maharaja Ranjit Singh was recently named the “Greatest Leader of All Time” in a British poll by ‘BBC World Histories Magazine’. Maharaja Ranjit Singh was a Sikh ruler and was known for his benevolence, valor, and care for his people. His rule in Punjab gave stability, harmony, progress, and prosperity to the society. He always identified himself with peasants and soldiers. He gave little importance to the crown and the throne. He did not assume the title of the king. He liked to be addressed by the plain and simple title of ‘singh sahib’ which applies to any member of the Sikh gentry. He refused to sit on the Mughal throne at Lahore and preferred to hold Darbar sitting in a cross-legged position in one or the other chair which did not have any semblance of royal throne. Sometimes, he held Darbar even in a more informal manner, sitting on a carpet and reclining on a velvet cushion. He referred to his government as khalsaji or sarkar khalsa. He was simply dressed in plain silk or pashmina in winter and white muslin in summer. He was firm about wearing his simple chieftain’s turban and never adorned himself with any royal emblem on his turban. These habits of the Maharaja may also be attributed to his hailing from the tribal peasant stock and the impact upon him of the rural culture of the Punjab. He adopted liberal policies towards all religions and treated them with magnanimity. People of all religions equally reciprocated his warm interest in their religions. Their religious beliefs and practices were fully respected by the state and they had unstinted freedom to carry on their worship in any way they liked. He and his royal court (Lahore Darbar) participated in fairs and festivals of all, even those festivals which were strictly religious. He did not interfere in the well-established customs, rites, and practices of the people. Old traditions and practices were respected and followed. In the words of F.S. Waheeduddin, ‘There was complete religious harmony during the reign of Maharaja Ranjit Singh”. All the communities looked upon him not only as their protector but also as one of themselves. The Lahore Darbar has always been more than just a political center—it is a cultural and spiritual hub. It has been a venue for grand celebrations, such as lohri, basant, holi, dussehra, diwali, id-ul-fitr and shab-i-barat. The participation of the Maharaja and his Darbar in these festivals made them even more significant. In the Lahore darbar, the festival of Basant was observed with great pomp and show.